TRUST AND INNOVATIVE WORK BEHAVIOR: - Auliyah, Nur; Fikri, Muhammad Ali; Wardana, Made Galih Wisnu (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The creative industry is an economic sector focused on creating and distributing products related to creativity, ideas, and innovation. In order to be competitive, the creative industry sector needs innovation. Trust is the basis for creating knowledge sharing between employees. Knowledge sharing creates new ideas, creativity, and experiences between employees. Therefore, this research focuses on the development of new ideas in order to create new creativity and innovation through trust and knowledge sharing between employees. This study aims to determine the effect of trust and innovative work behavior mediated by knowledge sharing. This study uses a quantitative data processing method using partial least squares analysis of structural equivalence modeling with SmartPLS 4.0 statistical tools. The sample of this study is 57 respondents in micro, small, and medium enterprises (MSMEs) in the creative industry sector in Yogyakarta. The results of this study show that trust significantly affects innovative work behavior, trust has an effect on knowledge sharing, knowledge sharing has an effect on innovative work behavior, and knowledge sharing mediates the effect of trust on innovative work behavior. Keywords: Knowledge Sharing; Trust; Innovative Work Behavior